1999
DOI: 10.1038/sj.onc.1202919
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated transfer of wild-type p53 gene sensitizes TNF resistant MCF7 derivatives to the cytotoxic effect of this cytokine: relationship with c-myc and Rb

Abstract: Tumor suppressor p53 is a nuclear transcription factor that blocks cell cycle progression and induces apoptosis. We have previously shown that the MCF7 resistance to the cytotoxic action of TNF correlates with p53 mutations. In the present study, we used a recombinant adenovirus carrying a wild-type p53 gene (Adwtp53) in order to investigate the e ect of wt p53 transfer on modulation of cell resistance to the cytotoxic action of TNF. Our data indicate that infection of TNF resistant MCF7 cells (1001 and MCF7/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…30 More recently, we have shown that adenovirus -based transfer of wtp53 gene increased sensitivity of cells with mutant p53 to the cytotoxic effect of TNF 31 by a mechanism independent of Bax and Bcl -2 expression but involving ROS production. 43 In the present study, we further examined the molecular basis of tumor resistance to the cytotoxic action of TNF and explored the wtp53-induced sensitization of TNF -resistant cells to the cytotoxic action of TNF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 More recently, we have shown that adenovirus -based transfer of wtp53 gene increased sensitivity of cells with mutant p53 to the cytotoxic effect of TNF 31 by a mechanism independent of Bax and Bcl -2 expression but involving ROS production. 43 In the present study, we further examined the molecular basis of tumor resistance to the cytotoxic action of TNF and explored the wtp53-induced sensitization of TNF -resistant cells to the cytotoxic action of TNF.…”
Section: Discussionmentioning
confidence: 99%
“…31 Several reports indicate that p53 can induce or potentiate apoptosis through a variety of mechanisms, e.g., by regulating the expression of genes that participate in the apoptotic response at the mitochondrial level, 45,46 a transcription -dependent p53 -induced alteration in the redox balance, 47 and /or through transcription -independent effects, 28,48,49 which may involve the translocation of p53 to mitochondrial membranes, facilitating their permeabilization. 50 Caspase activation (caspases-3 and -9) has also been connected to p53 -mediated cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The replication-deficient adenovirus vector Adwtp53 that harbors a human p53 gene driven by a SV40 virus early promoter in place of the E1 region has been described previously (19). The conditionally replicative adenovirus AdD24 that lacks 24 bp corresponding to amino acids 122 to 129 in the CR2 domain of E1A necessary for binding to Rb protein (20) and has a deleted E3 region and its derivative AdD24-p53 that carries a SV40 virus early-p53 expression cassette inserted in place of the deleted E3 region were described before (17).…”
Section: Nutlins and Recombinant Adenovirusesmentioning
confidence: 99%